Case Study on the Decision Making of Single Men to Marry Single-Parent Woman - Esti Pamularsih; Dyah Siti Septiningsih (Proceedings Series on Social Sciences & Humanities, 2021)
Marriage is a developmental task for individuals in the early adult phase. Normatively for a single man will choose a spouse as a single woman. This research aims to examine the decision-making of single men to marry single-parent women. This research uses a qualitative method with a case study approach. Data collection was carried out by semi-structured interviews using Miles and Huberman model data analysis techniques, namely the interactive model. The credibility of this research uses triangulation of sources, namely using the closest person to the informant to obtain valid data. There are several findings in the study, the first regarding the criteria of a partner, the second consideration before marriage, the third considers single-parent women as great women, and the fourth is responsibility. This is an essential point as an excuse for single men to marry single-parent women.